2020
DOI: 10.1002/adom.201901643
|View full text |Cite
|
Sign up to set email alerts
|

Organic Functional Molecule‐Based Single‐Crystalline Nanowires for Optical Waveguides and Their Patterned Crystals

Abstract: The deterministic manufacturing and patterning of high‐quality organic single crystal semiconductors are core opportunities and challenges for large‐scale integrated functional devices with high efficiency and high performance. As for the solution patterning for the fabrication of the organic semiconductors, various methods are reported to efficiently control the position, alignment, and size of organic structures. Nevertheless, the poor control of the dewetting dynamics of organic solution leads to the low cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Reproduced with permission. [43] Copyright 2020, Wiley-VCH. e) Fluorescence images of branched BIDB organic microrods.…”
Section: Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [43] Copyright 2020, Wiley-VCH. e) Fluorescence images of branched BIDB organic microrods.…”
Section: Dimensionmentioning
confidence: 99%
“…For example, in 2020, Zhang et al reported a method of using micropillar-structured templates with asymmetric wettability to construct patterned OFOW nanowires with precise geometry, high crystallinity, and flat morphology (Figure 5d). [43] The templates with lyophobic tops and lyophilic sidewalls can dominate the dewetting dynamics of a molecule solution and fabricate patterned OFOW precisely by limiting the liquid film in the gaps between the two micropillars and forming capillary tubes with square cross-sections. MFOWs with hetero-/homostructure can be used in optoelectronic circuits, such as optical logic gate function.…”
Section: Shapementioning
confidence: 99%
“…[17][18][19][20] As for molecule-based nano-optoelectronics, developing new methodology to make lateral heterostructures is also the prerequisite to realize some promising applications like organic laser, [21,22] field-effect light-emitting transistors, [23,24] flexible photodetectors, and so on. [25][26][27][28] Although delicate patterns of either nanoelectrodes, [29,30] or OSCs, [31][32][33][34][35][36] have been produced via a variety of methods, there still lacks a successful demonstration of organic laterally asymmetric heterojunction with both adjustable structure and key resolution better than 1 µm, i.e., the upper limit of exciton diffusion length in OSCs. [37,38] The major obstacle lies in their incompatibility of OSCs with standard photolithography procedures such as wet etch, dry etch and lift-off, which represent the most powerful and versatile fabrication tools at length scale of micrometers.…”
Section: Doi: 101002/smll202105306mentioning
confidence: 99%
“…Recently, organic crystals have been employed as a promising anisotropic light transducing media for the next-generation optical communication, [38,[42][43][44] especially in nonlinear optical waveguides, chiral information encoded waveguides and heterostructure waveguides. [45][46][47] Particularly, those crystals with plasticity or elasticity were found to have the capability to transduce light information in the highly bent state.…”
Section: Optical Waveguides and Amplified Spontaneous Emissionsmentioning
confidence: 99%